FUNDRAISING AND GRANT WRITING: FUNDING STRATEGIES - NAHAICHUK, Viktoriia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Fundraising and grant writing are becoming increasingly important elements of financial planning for nonprofit organizations and projects. Fundraising, as a strategy for raising funds through donations and pub- lic support, is a vital source of funding for organizations, enabling them to grow and fulfill their social mission.     Nowadays effective use of fundraising becomes a key factor in the success of nonprofit sectors. On the other hand, grant writing, which involves obtaining funding through competitive procedures and grant applications, allows organizations to receive financial support for specific  projects or programs. Since grants are often awarded for the implementation of innovative and socially significant initiatives, grant writing becomes an important mechanism for fostering change and societal development. The increasing complexity of the financial needs of nonprofit organizations underscores the relevance of fundraising and  grant writing as strategies for mobilizing financial resources to achieve their goals. The research is aimed at finding  effective methods and tools used to attract funding through fundraising and grant writing, starting with an idea and ending with its implementation. By analyzing the process from initial idea to successful project implementation, the most optimal approaches and strategies for achieving this goal have been identified. Methods used in this research include analysis of current trends and relevant data in the field of fundraising and grant writing, study of successful case studies, and conducting special surveys among experts and practitioners. Various aspects of fundraising, from strategy development to planning execution and result tracking, have been examined. There are diverse tools and strategies that can be utilized to attract funding through fundraising and grant writing. Key elements for successful project implementation include clear goal definition, effective communication planning, and stakeholder engagement. Additionally, strategic resource utilization and networking also play crucial roles in the success of fundraising and grant initiatives. Engagement and support of the community and stakeholders throughout the process significantly influence the outcome. Therefore, clear strategy definition, precise planning, and systematic project pro motion can help achieve the desired financial outcome.
Keywords: fundraising; communication plan; networking; non-profit organizations; funding strategies; resource management